2018
DOI: 10.1111/jre.12592
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrastructural analysis and histomorphometry of collagen bundles in the periodontal ligament using focused ion beam/scanning electron microscope tomography

Abstract: These findings indicate that collagen bundles in horizontal fiber areas have high strength and that the tooth is firmly anchored to the alveolar bone by the horizontal fibers, but is not secured evenly to the alveolar bone. The tooth is firmly anchored around the cervical area, creating a "slingshot-like structure." This study has provided further insights into the structure of the PDL and forms the basis for the development of more effective therapies for periodontal tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The experimental results reported by Natali et al show a softening phenomenon of the tissue under load repetition that may be caused by rearrangement of fibres . In the nonloading state, the fibrous network is partially disorganized with interweaved collagen fibres . This organization leads to a stiffer behaviour of the matrix than if the fibres were not interconnected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results reported by Natali et al show a softening phenomenon of the tissue under load repetition that may be caused by rearrangement of fibres . In the nonloading state, the fibrous network is partially disorganized with interweaved collagen fibres . This organization leads to a stiffer behaviour of the matrix than if the fibres were not interconnected.…”
Section: Introductionmentioning
confidence: 99%
“…16,26,30 In the nonloading state, the fibrous network is partially disorganized with interweaved collagen fibres. 31 This organization leads to a stiffer behaviour of the matrix than if the fibres were not interconnected. When the tissue is stretched, the local movement of the collagen fibres causes the fibrous network to become untangled, resulting in a softening phenomenon 31 that has been observed in other soft tissues, such as the arteries, 32 veins, 33 vaginal tissues, 34 and oesophageal tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human PDL is known as a heterogenous connective tissue mainly composed of fiber networks and bundles with different orientations and locations longitudinally. The PDL fibers around the cervical part of the tooth root are oriented horizontally, while the PDL in the middle part of the root consists of the oblique fibers [ 24 ]. An earlier study reported that as a result of sawing, the disruption of oblique fibers in the PDL within the transverse section can cause inevitable errors [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main role of the PDL is the anchoring of the tooth to the surrounding mandibular/alveolar bone and providing a space to allow tooth movement within the bone socket. This is mediated by bundles of collagen fibers ending as Sharpey’s fibers embedded in the cementum on one side and bone on the other ( Figures 3D,E ; Ho et al, 2007 ; Lee et al, 2015 ; Hirashima et al, 2020a ). Based on immunoelectron microscopy, Huang et al (1991) have proposed that periodontal and Sharpey’s fibers consist in co-fibrils of type I and type III collagens, which is supported by the similar flexibility of alfa-1 chains in both collagen types and their possible involvement in elastic energy storage during stretching ( Silver et al, 2002 ).…”
Section: Mesenchymes Specification and Differentiation During Developmentioning
confidence: 99%